(untitled) (Proceedings of International Educators Conference, 2023)
This article discusses the goals and objectives of the science of microbiology and epidemiology, as well as their history of development. Microbiology is the study of microorganisms, while epidemiology is the study of the patterns, causes, and effects of health and disease conditions in populations. The methods, results, and discussion sections outline the various scientific techniques, findings, and debates that have shaped these fields, with a focus on the historical context of their emergence. The article concludes with suggestions for future research and practice.